Vegetable Proteins : Non-sensitizing Encapsulation Agents for Bioactive Compounds (2017)
ABSTRACT: Plant-derived proteins are remarkable macromolecules of scientific interest because they represent an alternative to the animal-derived proteins and petroleum-derived polymers. Many food proteins especially those derived from animal sources could act as antigens in humans. For instance, milk proteins extracted from cows may cause food intolerance during infancy. Further, soybean, peanuts, tree nuts, fish, crustacean shellfish and egg proteins may act as antigens in 90% of children. Since the GI tract is permeable to intact antigens the oral intake of these proteins may generate gastrointestinal (50–80%), cutaneous (20-40%) and respiratory symptoms (4–25%). Most of these allergens are water-soluble glycoproteins that are resistant to acids and enzymes. Usually, these proteins have a small molecular weight (10,000–60,000 kDa), water solubility, glycosylation residues, and a relative resistance to heat and digestion. Allergenicity is less frequent in vegetable proteins due to their less flexible and non-compact structure. Allergenicity is also related to the resistance to proteolysis, post-translational glycosylation, presence of epitopes, and enzymatic proteolysis. Moreover, proteins serve as a coating material if structural modifications in the protein, either by physical, chemical or enzymatic mechanisms are conducted. As a result, their allergenicity is reduced, and their functional properties are enhanced.